Alcohol use among out-of-school youth in Iloilo city. - Cabaluna, Vanessa P.; Eler, Paul Candice Ellen; Gazo, Ella Catherine T.
The out-of-school youth, 13-22 years old, appears to have one of the greatest risk for alcohol use. This study was conducted to determine alcohol use among out-of-school youth in the city of Iloilo. The subjects of the study were 150 out-of-school youths, randomly selected from 15 barangays of the 6 districts of Iloilo City. Data for this research was gathered using an interview schedule. Results show that one hundred thirty one (87.33%) out of 150 out-of-school youth respondents had been initiated to alcoholic drinks. Their mean age of alcohol initiation was 15.81. Majority of these respondents usually drink beer (58.78%), followed by gin (13.74%), and tuba/lambanog (12.22%). Other choices include rum and brandy. Factors that influenced the respondents to drink alcohol included friends (67.94%), relatives (12.98%), father (9.16%). Other factors included personal decision, mass media, and mood/problems. Reasons for drinking alcoholic beverages include celebrations of special occasions (30.53%), leisure (18.32%), curiosity (15.27%), and sense of belongingness (12.98%). Other reasons incldue peer pressure, personal choice and personal problems. Reasons for not drinking incude personal choice (47.37%), health reasons (31.58%), family prohibits (15.79%), and religion prohibits (5.26%). Alcohol use is significantly associated with respondent's sex, involvement in organizations or community activties, smoking and use of prohibited drugs. There is no significant difference between alcohol use and family drinking status and with whom they are staying.